Protocols in In Vitro Hepatocyte Research - Vinken, Mathieu; Rogiers, Vera.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Humana, 2015)
This volume presents 30 state-of-the-art protocols and reviews to set up and apply primary hepatocyte cultures for research and screening purposes. The first part of the book focuses on the use of these particular liver-based in vitro models to study the different aspects of the hepatocyte life cycle, including cell growth, differentiation and cell death. The second part of the book is targeted towards the demonstration of the applicability of primary hepatocyte cultures, or liver-based in vitro models derived thereof, for functionality and toxicity testing. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step and readily reproducible laboratory protocols, and key tips on troubleshooting and avoiding known pitfalls.   Authoritative and practical, Protocols In In-Vitro Hepatocyte Research is intended for basic and applied researchers in the area of pharmacology and toxicology, both in academic and industrial settings.   .
Isolation And Culture Of Mouse Hepatocytes: Gender-Specific Gene Expression Responses To Chemical Treatments -- Cryopreservation of Hepatocytes -- Culture Conditions Promoting Hepatocyte Proliferation And Cell Cycle Synchronization -- Immortalized Human Hepatic Cell Lines For In Vitro Testing And Research Purposes -- Culture and Functional Characterization Of Human Hepatoma Hepg2 Cells -- Establishment And Characterization Of An In Vitro Model Of Fas-Mediated Hepatocyte Cell Death -- Serum-Free Directed Differentiation Of Human Embryonic Stem Cells To Hepatocytes -- Human Skin-Derived Precursor Cells: Isolation, Expansion And Hepatic Differentiation -- Generation Of Hepatocytes From Pluripotent Stem Cells For Drug Screening and Developmental Modeling -- Differentiation-Promoting Medium Additives For Hepatocyte Cultivation and Cryopreservation -- Co-Culture and Long-Term Maintenance Of Hepatocytes -- Primary Hepatocytes In Sandwich Culture -- Establishing Liver Bioreactors For In Vitro Research -- Epigenetic Modifications As Anti-Dedifferentiation Strategy For Primary Hepatocytes In Culture -- Transfection Of Primary Hepatocytes With Liver-Enriched Transcription Factors Using Adenoviral Vectors -- Transcriptomics Of Hepatocytes Treated With Toxicants For Investigating Molecular Mechanisms Underlying Hepatotoxicity -- Global Microrna Analysis In Primary Hepatocyte Cultures -- Mass Spectrometry-Based Proteomics For Relative Protein Quantification And Biomarker Identification In Primary Human Hepatocytes -- Targeted Metabolomics For Homocysteine-Related Metabolites In Primary Hepatocytes -- Measurement Of Cytochrome P450 Enzyme Induction And Inhibition In Human Hepatoma Cells -- Analysis Of Sinusoidal Drug Uptake Transporter Activities In Primary Human Hepatocytes -- Measurement Of Albumin Secretion As Functionality Test In Primary Hepatocyte Cultures -- Measurement Of Blood Coagulation Factor Synthesis In Cultures Of Human Hepatocytes -- Functionality Testing Of Primary Hepatocytes In Culture By Measuring Urea Synthesis -- Assay Of Bile Acid Conjugation And Excretion In Human Hepatocytes -- General Cytotoxicity Assessment By Means Of The MTT Assay -- Measurement Of Apoptotic And Necrotic Cell Death In Primary Hepatocyte Cultures -- Critical Factors In The Assessment Of Cholestatic Liver Injury in vitro -- In vitro Cell Culture Models Of Hepatic Steatosis -- Assessment Of Liver Fibrotic Insults in vitro.             .
Keywords: Pharmacology; Pharmacology/Toxicology.